(untitled) (Research, Society and Development, 2022)
The present study aimed to know the view of adolescents about safe sex practices and the most present influences when choosing the contraceptive method. This was an integrative review where the data search was carried out from April to May 2022, through a search in the databases: Scientific Electronic Library Online (SciELO) and Database on Nursing (BDENF). The inclusion criteria used were empirical scientific articles from research with human beings, master’s dissertation and doctoral theses, Brazilian studies, in Portuguese, full text available electronically, free of charge, and studies that addressed the proposed theme dated in the period of 2018 to 2022. Works that did not meet the guiding question of the research and studies in duplicates in more than one database were excluded. In addition, 11 articles were selected for analysis of the integrative review, and for better discussion they were divided into three categories: The influences on sexuality and the impact of early sexarche among adolescents, knowledge of adolescents about preventive measures related to the practice of sex insurance, and the family, school and health services in the dissemination of information focused on sexuality and the use of contraceptive methods among adolescents. Finally, the importance of the partnership between the three links that involve adolescents was highlighted: school, family and health services.